Resilient seed systems for climate change adaptation and sustainable livelihoods in the East Africa subregion. Report of the consultative workshop, 5-8 March 2019, Entebbe, Uganda - Recha, Tobias; Vernooy, Ronnie; Halewood, Michael; Otieno, G. (2019)
This report presents the main results of the consultative start-up workshop for the ‘Resilient seed systems in East Africa’ initiative which aims to combine and scale from the local to the global level, successful strategies, methods and tools that increase the timely availability, affordability and improved access by women and men farmers and their communities, to good-quality seed of a portfolio of crops and crop varieties, including novel crops and varieties that are better adapted to current and predicted future climate conditions.